Using role play in teaching for academic and occupational purposes in ITM teaching-learning situations / Siti Akmar Abu Samah (Universiti Teknologi MARA, Terengganu, 1992)
This article examines the favourable aspects of using role play in the teaching experience to the students undergoing academic and occupational training and learning in ITM. It discusses basic methodology of teaching with respect to the use of the technique. In practical terms, this technique can be used not only in language teaching-learning, but also in content subjects as discussed in the paper. Some suggestions are put forward to provide fundamental outlines for teachers to further developed the technique for their own purposes.